Common variants associated with blood lipid levels do not affect carotid plaque composition. Issue 1 (September 2015) - Siemelink, M.A.; van der Laan, S.W.; van Setten, J.; de Vries, J.P.P.M.; de Borst, G.J.; Moll, F.L.; den Ruijter, H.M.; Asselbergs, F.W.; Pasterkamp, G.; de Bakker, P.I.W.
Abstract: Introduction: Although plasma lipid levels are known to influence the risk of cardiovascular disease (CVD), little is known about their effect on atherosclerotic plaque composition. To date, large-scale genome-wide association studies have identified 157 common single-nucleotide polymorphisms (SNPs) that influence plasma lipid levels, providing a powerful tool to investigate the effect of plasma lipid levels on atherosclerotic plaque composition. Methods: In this study, we included 1443 carotid endarterectomy patients from the Athero-Express Biobank Study with genotype data. Plasma concentrations of high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC) and triglycerides (TG) were determined at the time of endarterectomy. Atherosclerotic plaques, obtained during surgery, were histologically examined. For all patients, we calculated weighted genetic burden scores (GBS) for all lipid traits on the basis of the available genotype data. Plasma lipid levels and GBS were tested for association with 7 histological features using linear and logistic regression models. Results: All GBS were associated with their respective plasma lipid concentrations (pHDL-C = 2.4 × 10 −14, pLDL-C = 0.003, pTC = 2.1 × 10 −6, pTG = 3.4 × 10 −8 ). Neither the measured plasma lipids, nor the GBS, were associated with histological features of atherosclerotic plaque composition. In addition, neither the plasma lipids nor the GBS were associated with clinical endpoints within 3 years of follow-up, with the notable exception of a negative association between HDL-C and composite cardiovascular endpoints. Conclusion: This study found no evidence that plasma lipid levels or their genetic determinants influence carotid plaque composition. Highlights: Genetic burden scores for plasma lipids (HDL-C, LDL-C, TC, TG) were associated with plasma lipid levels despite statin use. Neither plasma lipids nor genetic burden scores were associated with histology of the atherosclerotic plaque. Only HDL-C plasma levels were associated with cardiovascular events within 3 years.